Biochemical Mechanism of Human Immunodeficiency Virus Type 1 Reverse Transcriptase Resistance to Stavudine - Lennerstrand, Johan (American Society for Microbiology, 2001)
We have found a close correlation between viral stavudine (d4T) resistance and resistance to d4T-triphosphate at the human immunodeficiency virus type 1 reverse transcriptase (RT) level. RT from site-directed mutants with 69S-XX codon insertions and/or conventional zidovudine resistance mutations seems to be involved in an ATP-dependent resistance mechanism analogous to pyrophosphorolysis, whereas the mechanism for RT with the Q151M or V75T mutation appears to be independent of added ATP for reducing binding to d4T-triphosphate.